Desain Program Pembelajaran Berbasis Multiple Intelligences (Talent Focus) untuk Optimalisasi Kecerdasan dan Keterampilan Siswa Sekolah Dasar - Nurul Zikri Filina; Dian Erlita; Lindayani; Putri Fakhrina Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The importance of developing multiple intelligences as a basis for improving the intelligence and skills of elementary school students so that learning is more adaptive to individual potential. The purpose of this study is to produce a learning program design (Talent Focus) based on Multiple Intelligences to optimize student intelligence and skills. The study used the ADDIE development model with 91 fourth and fifth grade students and 4 teachers at Cot Keh Public Elementary School as subjects. Data were collected through observation, interviews, questionnaires, and expert validation, then analyzed using qualitative and quantitative descriptive techniques through the feasibility percentage and the N-Gain effectiveness test. The results showed that the Talent Focus program obtained an average feasibility of 84.3% (very feasible category) with an increase in student abilities of 0.63 (moderate-effective category), and received positive responses from teachers (84%) and students (88%). This program was declared feasible and effective to be implemented as a learning innovation that is able to develop dominant intelligence and improve critical thinking, creative, collaborative, and communication skills of elementary school students.